Gambaran Pengetahuan Orangtua Tentang Gizi, Asupan Makanan, Pola Asuh Orangtua, Jumlah Anggota Keluarga Pada Balita Gizi Buruk Di Rumah Sakit HNGV Dili Timor-Leste - Quiteria Libania Marques; Sugeng Maryanto (JURNAL GIZI DAN KESEHATAN, 2022)
Malnutrition has negative impact to human’s growth, development and well being. Children’s physical become short, thin, reduce intelligence, and risk of infection and even death. It caused by several factors including knowledge, food intake, parenting and number of family members. This study is to identify the description of parental knowledge about nutrition, food intake, parenting style, number of family members and number of children malnourished. The design of this research is descriptive with a survey approach. The population that used in this study was mothers and children between 1 to 5 years who were malnourished at the HNGV Dili Hospital Timor-Leste with a sample of 71 people who were taken by total sampling technique. The measuring instrument is used a questionnaire. The data were analyzed using the frequency distribution formula and processed using the SPSS data processing program. Mothers of severely malnourished children under five had parental knowledge about nutrition, most of them were in sufficient category (54.9%), had mostly unbalanced food intake (57.7%), had most of the parenting styles in poor categories (53.5%). ) and has a large number of family members (> 4 people) (60.6%). Mothers of malnourished children have sufficient knowledge about nutrition, but the food intake given is not balanced, has poor parenting style and has a large number of family members. ABSTRAKGizi buruk berdampak pada tumbuh kembang yang tidak sempurna. Tubuh anak bisa menjadi pendek, kurus, menurunkan kecerdasan, berisiko terkena infeksi hingga kematian. Hal ini dipengaruhi beberapa faktor diantaranya pengetahuan, asupan makanan, pola asuh dan jumlah anggota keluarga. Penelitian ini bertujuan mengetahui gambaran pengetahuan orangtua tentang gizi, asupan makanan, pola asuh orangtua, jumlah anggota keluarga pada balita gizi buruk. Desain penelitian adalah ini deskriptif dengan pendekatan survey.Populasi dalam penelitian ini ibu dan balita 1-5 tahun yang mengalami gizi buruk di Rumah Sakit HNGV Dili Timor-Leste dengan sampel sebanyak 71 orang yang diambil dengan teknik total sampling. Alat ukur yang digunakan adalah kuesioner. Data di analisis menggunakan rumus distribusi frekuensi diolah menggunakan program pengolahan data SPSS. Ibu balita gizi buruk mempunyai pengetahuan orang tua tentang gizi sebagian besar kategori cukup (54,9%), mempunyai asupan makanan sebagian besar kategori tidak seimbang (57,7%), mempunyai pola asuh sebagian besar kategori kurang (53,5%) dan mempunyai jumlah anggota keluargasebagian besar kategori besar (> 4 orang) (60,6%). Ibu balita gizi buruk mempunyai pengetahuan yang cukup tentang gizi, tetapi asupan makanan yang diberikan tidak seimbang, pola asuh yang kurang baik dan jumlah anggota keluargayang besar.